2013
DOI: 10.1002/etc.2231
|View full text |Cite
|
Sign up to set email alerts
|

Observations of limited secondary effects to benthic invertebrates and macrophytes with activated carbon amendment in river sediments

Abstract: Amendment of activated carbon to sediments has been shown to effectively reduce the bioavailability of hydrophobic organic contaminants, but concerns have been raised about the potential toxicological impacts of administering a strong sorbent into sediments. The present study provides a summary of several investigations carried out as part of a pilot-scale study in a river to understand the secondary effects of activated carbon added to reduce the bioavailability of sediment-associated polychlorinated biphenyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
1

Year Published

2015
2015
2018
2018

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 44 publications
1
41
1
Order By: Relevance
“…Other studies on community responses to AC have often showed less negative effects, where causes for less susceptibility may be attributed to factors keeping up the resilience in these systems. For example, the larger AC particles (100–200 μm) and relative organic carbon-rich river sediment (TOC 4–6%) may explain the limited negative effects to a fresh water community in Grasse River (Beckingham et al 2013). Moreover, the mild initial effects and full recovery of the benthic community 1 year after exposure to powdered AC in an un-contaminated fresh water experimental ditch may also be attributed to less stress due to organic carbon rich (TOC 8%) sediment (Kupryianchyk et al 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies on community responses to AC have often showed less negative effects, where causes for less susceptibility may be attributed to factors keeping up the resilience in these systems. For example, the larger AC particles (100–200 μm) and relative organic carbon-rich river sediment (TOC 4–6%) may explain the limited negative effects to a fresh water community in Grasse River (Beckingham et al 2013). Moreover, the mild initial effects and full recovery of the benthic community 1 year after exposure to powdered AC in an un-contaminated fresh water experimental ditch may also be attributed to less stress due to organic carbon rich (TOC 8%) sediment (Kupryianchyk et al 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Further, a few studies on benthic community level exposed to AC also show contradictory results. No negative effects were shown with granular AC in a fresh water benthic community in Grasse River, USA (Beckingham et al 2013). A benthic community in a fresh water ditch (Veenkampen, The Netherlands) showed an initial perturbation followed by recolonization and recovery 1 year after exposure of fine particle AC (Kupryianchyk et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Greater than 99% reductions in PCB aqueous equilibrium concentrations were observed during the third year of postplacement monitoring in plots where the AC dose in the 0‐ to 15‐cm layer was 4% or greater (Figure ), effectively demonstrating that PCB flux from sediments to surface water was almost completely contained. AC addition decreased PCB bioavailability as measured by in situ and ex situ bioaccumulation testing (using Lumbriculus variegatus ). The overall decrease improved during the 3‐year, post‐placement monitoring period, with greater than 90% reductions observed during the third year of post‐placement monitoring in plots where the AC dose in the 0‐ to 15‐cm layer was greater than 4% (Figure ). Benthic recolonization occurred rapidly after application and no changes to the benthic community structure or number of individuals were observed in AC amendment plots relative to background (Beckingham et al ). In laboratory studies using site sediment, aquatic plants grew at a moderately reduced rate (approximately 25% less than controls) in sediment amended with a dose of greater than 5% AC. The reduced growth rate was likely attributable to nutrient dilution of the sediment (Beckingham et al ). Although other project data (not shown) indicated the AC amendment slightly increased the erosion potential of sediments (although within the range of historical data for native sediments), all of the delivered AC remained in the sediments throughout the 3‐year, post‐placement monitoring period. Up to several centimeters of relatively clean, newly deposited sediment accumulated on the sediment surface in the pilot area over the 3‐year, postplacement monitoring period.…”
Section: Demonstrating Efficacy In the Fieldmentioning
confidence: 99%
“…Benthic recolonization occurred rapidly after application and no changes to the benthic community structure or number of individuals were observed in AC amendment plots relative to background (Beckingham et al ).…”
Section: Demonstrating Efficacy In the Fieldmentioning
confidence: 99%
See 1 more Smart Citation